The UN SDGs as a global ‘directive shift’ and the institutionalization of sustainability research - Alesia A. Zuccala; Anna Leoncini; Andrea Bonaccorsi (PLoS ONE, 2026)
This paper examines how the UN Sustainable Development Goals (SDGs) shape the institutionalization of sustainability research within scholarly publishing. We argue that the SDGs operate as a globally endorsed form of external research agenda-setting, constituting a “directive shift” in science. Focusing on SDG 04 (Quality Education), SDG 08 (Decent Work and Economic Growth), and SDG 13 (Climate Action), we analyse changes in Scopus-indexed journals from 1990 to 2024. Using large-scale bibliometric data, we classify ( n = 30,604) journals by activity level, age (newborn, young, mature, established), disciplinarity, publishing model, and long-term survival across publication thresholds ( k = 1, 3, 5, 10). Results reveal a sustained increase in journal participation related to SDG-related publishing, with pronounced entry surges around major international agreements in 2005 and 2015. Participation is driven primarily by young and mature journals, while established journals contribute a comparatively small share of new entrants. Further analysis of established titles reveals that top-ranked (Q1) core journals are more prominent in SDG 13 than in SDG 04 and SDG 08, suggesting uneven integration across disciplinary hierarchies. Multidisciplinary and open-access journals dominate entry patterns, and survival rates increase at higher publication thresholds, indicating sustained engagement over time. Overall, these structural dynamics suggest that the SDGs operate as a directive shift, contributing to the progressive consolidation of sustainability research within the journal system.